1998
DOI: 10.1128/mcb.18.4.1844
|View full text |Cite
|
Sign up to set email alerts
|

Anisomycin Selectively Desensitizes Signalling Components Involved in Stress Kinase Activation and fos and jun Induction

Abstract: Anisomycin, a translational inhibitor secreted by Streptomyces spp., strongly activates the stress-activated mitogen-activated protein (MAP) kinases JNK/SAPK (c-Jun NH 2 -terminal kinase/stress-activated protein kinase) and p38/RK in mammalian cells, resulting in rapid induction of immediate-early (IE) genes in the nucleus. Here, we have characterized this response further with respect to homologous and heterologous desensitization of IE gene induction and stress kinase activation. We show that anisomycin acts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
121
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(131 citation statements)
references
References 61 publications
9
121
1
Order By: Relevance
“…Our data conflict with previous reports that ANX activates JNK and p38 MAPK, but does not activate ERK cascades (Hazzalin et al, 1998). In other studies, however, ANX-induced activation of the ERK1/2 signaling pathway was observed in MCAS cells (Konishi et al, 2004).…”
Section: Discussioncontrasting
confidence: 57%
“…Our data conflict with previous reports that ANX activates JNK and p38 MAPK, but does not activate ERK cascades (Hazzalin et al, 1998). In other studies, however, ANX-induced activation of the ERK1/2 signaling pathway was observed in MCAS cells (Konishi et al, 2004).…”
Section: Discussioncontrasting
confidence: 57%
“…41 These distinct functions of c-Jun might be determined by the interplay with additional factors such as the interaction with other AP-1 members. Similar to c-Jun, other AP-1 members can also be induced by DNA-damaging signals, 42,43 indicating their potential involvement in promoting apoptosis with c-Jun. The data presented here show that c-Jun, JunB and FosB are activated by chemotherapeutic drugs to regulate DNp73 degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Similar effects on protein degradation may occur when particularly high doses of anisomycin are delivered locally into specific brain regions, such as the hippocampus or amygdala, because higher doses may take longer to be eliminated from the brain. Additionally, anisomycin is known to have effects on mitogen-activated protein kinase (33) and catecholamines (34), so one needs to exercise caution when interpreting these results as implicating de novo protein synthesis.…”
Section: Discussionmentioning
confidence: 99%